A Grammar and Dictionary of Tayap The Life and Death of a Papuan Language - Kulick, Don (Pacific linguistics ;, 2019)
Tayap is a small, previously undocumented Papuan language, spoken in a single village called Gapun, in the lower Sepik River region of Papua New Guinea. The language is an isolate, unrelated to any other in the area. Furthermore, Tayap is dying. Fewer than fifty speakers actively command it today. Based on linguistic anthropological work conducted over the course of thirty years, this book describes the grammar of the language, detailing its phonology, morphology and syntax. It devotes particular attention to verbs, which are the most elaborated area of the grammar, and which are complex, fusional and massively suppletive.The book also provides a full Tayap-English-Tok Pisin dictionary. A particularly innovative contribution is the detailed discussions of how Tayap''s grammar is dissolving in the language of young speakers. The book exemplifies how the complex structures in fluent speakers' Tayap are reduced or reanalyzed by younger speakers. This grammar and dictionary should therefore be a valuable resource for anyone interested in the mechanics of how languages disappear. The fact that it is the sole documentation of this unique Papuan language should also make it of interest to areal specialists and language typologists.